An Initial Exploration of Auspicious Patterns in Traditional Chinese Sculpture - Cao, Yue (International Journal of Social Sciences and Public Administration, 2025)
Nowadays, the forms of auspicious patterns in traditional sculpture vary widely, rich in connotation and profound in significance, embodying the thought-provoking traditional cultural connotations. The emergence of auspicious patterns is an important outcome of the millennia-long accumulation of historical and folk culture of the Chinese nation. As a unique cultural and artistic phenomenon, it not only encapsulates the wisdom of the ancient Chinese but also contains deep philosophical thoughts of humanity, further enriching humanistic ideas and carrying profound cultural significance. Based on this, the article first overviews the development history of traditional Chinese auspicious patterns, then summarizes their meanings, characteristics, and types, and finally analyzes the appearance design of traditional Chinese auspicious patterns, providing a reference for relevant scholars to explore and discuss.